ISLAM DAN POLITIK (PEREMPUAN) - Tobibatussa’adah Tobibatussa’adah (Postgraduate State Islamic Institute (IAIN) Metro, 2015)
Islam is a perfect religion that has given the status of women, including in matters of politics. The story of the queen Bilqis delivered the Koran is one proof that there are women who participate in the political domain to become head of state. Male female equality has been clearly established, although not pulgar but very elegant. The position of women in Islam has been placed in a fair, egalitarian, and respectable. Historically, women are also much involved in the political sphere as political actors by allegiance to the prophet, or participate in a joint struggle of the men on the battlefield. So based on the rules that have been established al-Quran and Hadith and historical legitimacy can be argued that political Islam is very appreciative of women, and women have equal footing with men in politics.